Scalable Thread Scheduling in Asymmetric Multicores for Power Efficiency - Rodrigues, Rance; Annamalai, Arunachalam; Koren, Israel; Kundu, Sandip (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
The emergence of asymmetric multicore processors(AMPs) has elevated the problem of thread scheduling in such systems. The computing needs of a thread often vary during its execution (phases) and hence, reassigning threads to cores(thread swapping) upon detection of such a change, can significantly improve the AMP's power efficiency. Even though identifying a change in the resource requirements of a workload is straightforward, determining the thread reassignment is a challenge. Traditional online learning schemes rely on sampling to determine the best thread to core in AMPs. However, as the number of cores in the multicore increases, the sampling overhead may be too large. In this paper, we propose a novel technique to dynamically assess the current thread to core assignment and determine whether swapping the threads between the cores will be beneficial and achieve a higher performance/Watt. This decision is based on estimating the expected performance and power of the current program phase on other cores. This estimation is done using the values of selected performance counters in the host core. By estimating the expected performance and power on each core type, informed thread scheduling decisions can be made while avoiding the overhead associated with sampling. We illustrate our approach using an 8-core high performance/low-power AMP and show the performance/Watt benefits of the proposed dynamic thread scheduling technique. We compare our proposed scheme against previously published schemes based on online learning and two schemes based on the use of an oracle, one static and the other dynamic. Our results show that significant performance/Watt gains can be achieved through informed thread scheduling decisions in AMPs.